In silico characterization of selected orchids’ hmg-coa reductases - Nurul Syazana Aqila, Muhammad Zawawi (2025)
HMG-CoA reductase (HMGR) was an essential enzyme for producing mevalonate, a key component of floral scent in orchids. It acted as a catalyst in the mevalonate pathway. This process yielded various isoprenoid compounds, including those contributing to the floral aroma. This study investigated the structure and function of HMGR and its homologous proteins in five orchid species which were Vanda Mimi Palmer, Phalaenopsis equestris, Dendrobium nobile, Dendrobium catenatum, and Vanilla planifolia, using an in silico approach.Amino acid sequences available in the NCBI GenBank were utilized to perform homology modeling and predict the three-dimensional (3D) structures of HMGR and its related proteins. The reliability of these structural models was validated using VERIFY 3D, PROCHECK, and ERRAT tools. The study aimed to predict the 3D-protein structure of the selected orchids' HMG-CoA reductases and homologous proteins using a homology modeling approach and to investigate the binding positions of potential ligands to the 3D structure of these enzymes by molecular docking. Active pocket regions (R1 and R2) were identified using CASTp, where R1 was the predicted pocket binding site of the selected orchid HMGRs and homologous proteins, while R2 was the predicted pocket binding site for 8ECG. Molecular docking experiments were conducted to evaluate the binding sites and affinities of potential substrates (HMG-CoA, Acetyl-CoA, and Acetoacetyl-CoA) and their product, mevalonate. Protein-ligand docking studies were performed using Autodock Vina to predict the orientation of a ligand bound to the protein and compare it with the predicted active site pocket analysis. This study contributed to a deeper understanding of the molecular and functional properties of HMGR and its homologous proteins in orchids. These insights enhanced knowledge of floral scent biosynthesis, particularly the enzymatic pathways involving HMG-CoA reductases, and provided valuable information for potential applications in horticulture, the fragrance industry, and related fields.